2012
DOI: 10.1042/cbi20110329
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin resistance induced by decreased apoptotic activity in non‐small‐cell lung cancer cell lines

Abstract: We have investigated defective steps in apoptosis that might account for the development of resistance. For this purpose, A549 and Calu1 NSCLC (non-small-cell lung cancer) cell lines were treated with cisplatin to obtain resistant sub-lines. Gene expression profiles and the phosphorylation status of the BAD (Bcl-2/Bcl-XL-antagonist, causing cell death) protein were determined for each cell line. Cell death and cytochrome c release were analysed after treating cell lines with their appropriate cisplatin doses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 6 publications
4
23
0
Order By: Relevance
“…It is well-established that p53 plays a central role in cisplatin-induced apoptosis independent of caspase-8 [13][14][15]. Similarly, we observed that cisplatin caused 10% cell death in A549 and H522 cells regardless of c-Src or caspase-8, which was prevented from the pancaspase inhibitor, zVAD-fmk ( Fig.…”
Section: C-src-induced Caspase-8 Phosphorylation In Lung Adenocarcinosupporting
confidence: 66%
“…It is well-established that p53 plays a central role in cisplatin-induced apoptosis independent of caspase-8 [13][14][15]. Similarly, we observed that cisplatin caused 10% cell death in A549 and H522 cells regardless of c-Src or caspase-8, which was prevented from the pancaspase inhibitor, zVAD-fmk ( Fig.…”
Section: C-src-induced Caspase-8 Phosphorylation In Lung Adenocarcinosupporting
confidence: 66%
“…A cisplatin-resistant subline of A549 and a gefitinib-resistant subline of PC9 were established by repeated subculturing with gradual increasing in the cisplatin (2, 4, 6, 8 and 10  μ M) or gefitinib concentration (4, 8, 16, 20 and 40  μ M) over a 3-month period. 52 In addition, A549, PC9, SW480 and SKCO1 cell lines with stable overexpression or knockdown of ZNF32 were constructed as described previously. 35 …”
Section: Methodsmentioning
confidence: 99%
“…These mechanisms of resistance primarily involve the abnormal expression of drug transporters and drug metabolizing enzymes in cells (25), increased DNA damage repair (26), abnormal regulation of cell cycle and apoptosis-related protein expression (27).…”
Section: Discussionmentioning
confidence: 99%